Evangelium als literarische Anweisung: Theologische Anmerkungen zu einem Buch von Gerhard Hahn - Bieritz, Karl-Heinrich (Jahrbuch für Liturgik und Hymnologie, 1983)
Gerhard Hahn presents a scholarly analysis of the spiritual songs of Luther in his book The Use of the Gospel as a Literary-Critical Tool ("Evangelium als literarische Anweisung"). Because of the nature of the topic and method it is necessary to constantly apply theological argumentation and interpretation. What is particularly new about these hymns of Luther is that here too, salvation is delivered through the Word, with all the serious consequences of this proposition. Bieritz sees the task of his discussion to lie not only within an evaluative and critical report, but rather in posing more challenging questions which surpass the competence of the Linguist, but logically follow Hahn's article. For example, in Luther's concept is there danger of limiting preaching only to the doctrine? And could it be possible that today's communicative situation once again requires a new impulse, which would contrast it to Luther's system?